2004
DOI: 10.1097/01.asn.0000122826.40921.d7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Perlecan Synthesis and Induction of TGF-β1 in Human Peritoneal Mesothelial Cells Due to High Dialysate Glucose Concentration

Abstract: Abstract. Prolonged exposure of the peritoneal mesothelium to high dialysate glucose concentrations reduces anionic sites that are critical to its selective permeability, thereby impairing the peritoneal transport properties in patients on long-term peritoneal dialysis (PD). Perlecan, an anionic heparan sulfate proteoglycan, is pivotal to the selective permeability of basement membranes, and high glucose concentrations modulate its synthesis in mesangial cells. The effect of glucose on perlecan expression in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…In areas where mesothelial cells are still apparent, changes observed are similar to those mentioned above with a loss of microvilli and cell-cell contact [81, 82]. Peritonitis also induces the loss of the underlying basement membrane and promotes extensive interstitial fibrosis attributed to increased synthesis of matrix proteins and a concomitant loss of decorin [3, 38, 77, 83]. Acute infiltration of inflammatory cell into the submesothelium is also noted, which may account at least in part, to the expansion of the interstitial.…”
Section: Changes To the Peritoneal Membrane During Pd And Peritonitismentioning
confidence: 94%
See 1 more Smart Citation
“…In areas where mesothelial cells are still apparent, changes observed are similar to those mentioned above with a loss of microvilli and cell-cell contact [81, 82]. Peritonitis also induces the loss of the underlying basement membrane and promotes extensive interstitial fibrosis attributed to increased synthesis of matrix proteins and a concomitant loss of decorin [3, 38, 77, 83]. Acute infiltration of inflammatory cell into the submesothelium is also noted, which may account at least in part, to the expansion of the interstitial.…”
Section: Changes To the Peritoneal Membrane During Pd And Peritonitismentioning
confidence: 94%
“…Although the nature of these anionic sites was not further investigated by these researchers, it is possible that perlecan may contribute at least in part to the anionic staining. We have demonstrated that perlecan expression is predominately observed within the mesothelium and underlying basement membrane in peritoneal specimens obtained from new PD patients [38]. Mesothelial expression of perlecan decreased with increasing duration on PD with a concomitant increase in the submesothelium [38].…”
Section: Changes To the Peritoneal Membrane During Pd And Peritonitismentioning
confidence: 99%
“…Lentivirus titers were determined by transfecting human embryonic kidney 293 T cells with a dilution series of the viral suspension, and lentivirus samples with a titer of 4 Â 10 8 transfection units/mL were stored at À80 C. 23,24 Peritoneal Exposure Model in Rats A chronic infusion model of nonuremic animal PD was used, as described previously. 6 …”
Section: Ethics Statementmentioning
confidence: 97%
“…Some researchers 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 have found that the growth and proliferation of HPMCs significantly changes when fibrosis develops in the PM after HG stimulation, followed by the cell cycle progression. 6 Cell proliferation could not be affected or even be inhibited at the initial stimulation time for 48 hours, and then had an abnormal proliferation and cell cycle progress at the following HG stimulation days. Thus, the inhibition of growth and the induction of cell cycle arrest of HPMCs might contribute to protection against PM fibrosis.…”
mentioning
confidence: 97%
“…Increasing evidence has shown that transforming growth factor (TGF)-␤ is a key mediator of experimental and human peritoneal fibrosis associated with peritoneal dialysis (PD) [5] . In vitro, peritoneal mesothelial cells are the major source of TGF-␤ 1 production in response to high glucose, which leads to extracellular matrix (ECM) accumulation by increasing the synthesis of ECM proteins while reducing their degradation [6,7] . In long-term CAPD patients, the concentrations of TGF-␤ 1 in PD effluents are significantly elevated, particularly in those with peritonitis [8,9] .…”
Section: Treatment Of Established Peritoneal Fibrosis By Gene Transfementioning
confidence: 99%